Evaluation and treatment of isolated sphenoid sinus diseases. Issue 1 (February 2016) - Tang, Ing Ping; Brand, Yves; Prepageran, Narayanan
Abstract : Purpose of review: To review cause, clinical evaluation, medical and surgical management of isolated sphenoid sinus diseases. Recent findings: Early diagnosis of isolated sphenoid sinus diseases requires a high index of clinical suspicion and appropriate radiological imaging. Sphenoid sinus can be approached endoscopically via a few different surgical techniques. Summary: Isolated sphenoid sinus diseases are uncommon, with nonspecific clinical presentation. Early diagnosis requires a high index of clinical suspicion, proper endoscopic nasal examination, and appropriate radiological imaging. Surgical intervention is the primary treatment modality for most of the isolated sphenoid sinus diseases. Endoscopic endonasal approach to sphenoid sinus is the technique of choice. The location of sphenoid sinus disease, the extent of the surgery, and anatomic configuration of the sphenoid sinus are the main factors that help to decide the most suitable surgical approach to the sphenoid sinus.